Efektywność w gospodarce globalnej - korporacje transnarodowe - Kozuń-Cieślak, Grażyna ("Efficiency in the Global Economy - International Corporations", 2005)
Efficiency means the use of economic resources in the most effective way. The dynamic development of the world civilization that has been observed during several past centuries gave the term of efficiency special importance, making it the subject of evaluation in many fields of economic operations both in the microeconomics and macroeconomics analysis. On the verge of 21st century business is becoming more and more international so the term of global efficiency seems to aspire to became a new paradigm in the theory of economics. The paper presents a synthetic review of history of economic thought in the context of economic growth determinants. The evolution of these determinants pushed the world economy onto the course of the progressive globalization. In the paper, the rank of corporations, which activity is a specific efficiency test of running business in the conditions of the world open market, has been presented too.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 201-213